Social Worker through the Lens of Professional Competences in the Czech Republic - Stárek, Lukáš (International Journal of Membrane Science and Technology, 2023)
Each profession has its own requirements, legal norms and we also work with the personal aspect of the worker. This professional text provides a description of the professional nature of the social worker in the Czech Republic and points out the developments that should reflect the upcoming changes. So what are the prerequisites for performing social work? Of course, we are aware that in the application of the situational approach, the personal setting of the social worker is only one side of the coin, the other side being the organisational and legislative conditions for the performance of social work by a given worker. However, based on our findings, it appears that personal setting plays a slightly more significant role. Since 2006, the Czech Republic has had legislation regulating the nature of social services, and in view of the reflection, there is new talk of necessary changes.